2001
DOI: 10.1007/3-540-45114-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Quantization of Constrained Systems

Abstract: The present article is primarily a review of the projection-operator approach to quantize systems with constraints. We study the quantization of systems with general first-and second-class constraints from the point of view of coherent-state, phase-space path integration, and show that all such cases may be treated, within the original classical phase space, by using suitable path-integral measures for the Lagrange multipliers which ensure that the quantum system satisfies the appropriate quantum constraint co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 36 publications
0
45
0
Order By: Relevance
“…The integration with respect to the unknown Φ β constraints will modify the integration measure from dλ α to a non − linear integration measure Dλ α (T = t i − t f ). This allows to represent the physical evolution operator in a form which is similar with to the result given by [36]:…”
Section: The Methods Of Quantum Constraintsmentioning
confidence: 99%
“…The integration with respect to the unknown Φ β constraints will modify the integration measure from dλ α to a non − linear integration measure Dλ α (T = t i − t f ). This allows to represent the physical evolution operator in a form which is similar with to the result given by [36]:…”
Section: The Methods Of Quantum Constraintsmentioning
confidence: 99%
“…It was concluded that the Abelian conversion method is preferable because it involves no extrinsic geometry in the results. For this and other reasons it was used in the beautiful projection operator approach to path integral quantization of constrained systems [20] aiming at quantizing the gravity [21]. But is it possible to generalize the above result to other surfaces?…”
Section: Abelian Conversion Methodsmentioning
confidence: 99%
“…Covariant quantum gravity. The projector can be expressed as a phase space path integral as is demonstrated by Klauder [12] for general constrained systems. This phase space integral can also be derived from a sum over geometries approach to quantum gravity, as has been investigated in detail by Teitelboim [29,31], forging the link between covariant and canonical frameworks.…”
Section: Canonical Vs Covariantmentioning
confidence: 99%
“…12 The reason that we chose to include a sum over triangulations initially is that it will play an important role in the following. The above procedure is also necessary for gravity in higher dimensions where we no longer have triangulation independence.…”
Section: Spin-foam Models and Loop Quantum Gravitymentioning
confidence: 99%